Effect of Si3N4 diluent on direct nitridation of silicon powder. Issue 8 (1st June 2019) - Jin, Xing; Xing, Pengfei; Zhuang, Yanxin; Kong, Jian; Jiang, Shengnan; Wei, Donghui
Abstract: To investigate the effect of the Si3 N4 diluent on the direct nitridation of silicon powder, the direct nitridation of silicon powder doped with different contents of α-Si3 N4 and β-Si3 N4 diluents was studied in detail. The phase constituent and microstructure of the products were detected using X-ray diffraction and scanning electron microscopy. Moreover, the weight changes and heat flow changes in the samples in the heating-up stage were investigated using thermogravimetric and differential scanning calorimetry. The results revealed that both the α-Si3 N4 diluent and the β-Si3 N4 diluent can accelerate the nitridation by decreasing the oxygen content in silicon powder. It was also revealed that both the α-Si3 N4 diluent and the β-Si3 N4 diluent can promote the formation of α-Si3 N4 by decreasing the extensive-nitridation temperature. The determination of the relationship between heat and temperature changes revealed that when an identical amount of silicon and Si3 N4 absorb an equal amount of heat, the temperature increment of the former is approximately 5.8 times that of the latter. Thus, the α-Si3 N4 diluent and the β-Si3 N4 diluent mainly function as heat accepters in the direct nitridation of silicon powder. They can absorb the additional heat released from the reaction between silicon and nitrogen and thus hinder the formation of the liquid phase in the nitridation process, thereby inhibiting the formation of an agglomerate phase and short needle-like Si3 N4 as products.